Educating musicians for sustainability - Reid, Anna, 1963-; Petocz, Peter (ISME global perspectives in music education series., 2022)
"Educating Musicians for Sustainability investigates the ways in which sustainability plays an important role in the education and professional preparation of musicians. It attempts to put into practice the aspirations of the United Nations Decade of Education for Sustainable Development (2005-2014) to integrate sustainability into education at all levels and disciplines. Organised around the four 'pillars of sustainability' - environmental, social, economic and cultural - aspects of music education reveal a multitude of intersections. Identifying and exemplifying these intersections assists aspiring musicians to develop a broader view of the profession of music as a human endeavour that is intimately related to the world in which they are living"--